Blockchain, Self-Sovereign Identity and Digital Credentials: Promise Versus Praxis in Education - Grech, Alex; Sood, Ira; Ariño, Lluís (Frontiers in Blockchain, 2021)
Blockchain’s versatility is primarily due to its immutable and almost indestructible nature. These attributes have caught the attention of researchers and developers interested in applications and environments where the need for the integrity of identity and content are as paramount as the safe delivery and record of transactions. Self-sovereign digital identity in particular is often cited as a human right that nation states need to embrace with as much conviction as education and lifelong learning are considered to be a public good. Although the blockchain has long been identified as an opportunity for driving much-needed change in the core processes of the education sector, use cases to date have been limited in scope and execution, with blockchain advocates and education policy makers seemingly disconnected on fundamental issues such as governance, self-sovereignty, interoperability, choice of blockchain platforms and overall trust in standards and the integrity of the infrastructure. This article is primarily interested in the affordances of the technology as a public good for the education sector. It levers on the lead author’s perspective as a mediator between the blockchain and education sectors in Europe on high-profile blockchain in education projects to provide a snapshot of the challenges and workable solutions in the blockchain-enabled, European digital credentials sector.